2019
DOI: 10.1177/0957650919887888
|View full text |Cite
|
Sign up to set email alerts
|

Off-design performance improvement of twin-shaft gas turbine by variable geometry turbine and compressor besides fuel control

Abstract: A novel procedure for finding the optimum values of design parameters of industrial twin-shaft gas turbines at various ambient temperatures is presented here. This paper focuses on being off design due to various ambient temperatures. The gas turbine modeling is performed by applying compressor and turbine characteristic maps and using thermodynamic matching method. The gas turbine power output is selected as an objective function in optimization procedure with genetic algorithm. Design parameters are compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…To evaluate the performance of a gas turbine due to a physical fault, ambient condition variations, variable inlet guide valve drift and bleed air leakage, several studies have been conducted to investigate performance deviations from the clean condition. Sepehr et al [ 14 ] developed a new method for determining the ideal values of design parameters for industrial twin-shaft gas turbines, variable-geometry turbines, and compressors, with fuel control operations at varying ambient temperatures also being described. The focus of their research was an on–off design with varying ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the performance of a gas turbine due to a physical fault, ambient condition variations, variable inlet guide valve drift and bleed air leakage, several studies have been conducted to investigate performance deviations from the clean condition. Sepehr et al [ 14 ] developed a new method for determining the ideal values of design parameters for industrial twin-shaft gas turbines, variable-geometry turbines, and compressors, with fuel control operations at varying ambient temperatures also being described. The focus of their research was an on–off design with varying ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the researchers concluded that integrating inlet air cooling can reduce the engine performance deterioration caused by ambient condition variation, particularly in hot climate zones. For industrial twin-shaft gas turbines that have variable geometry in the compressors and turbines, in addition to control of fuel running at various ambient temperatures, Sepehr et al [ 36 ] created and discussed an innovative approach. The research concentrated on off-design with fluctuating environmental temperatures.…”
Section: Introductionmentioning
confidence: 99%